2020
DOI: 10.1136/heartjnl-2019-315672
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary issues in severe aortic stenosis: review of current and future strategies from the Contemporary Outcomes after Surgery and Medical Treatment in Patients with Severe Aortic Stenosis registry

Abstract: Contemporary Outcomes after Surgery and Medical Treatment in Patients with Severe Aortic Stenosis (CURRENT AS) registry was a large Japanese multicentre retrospective registry of consecutive patients with severe aortic stenosis (AS) before introduction of transcatheter aortic valve implantation. We sought to overview the data from the CURRENT AS registry to discuss the three major contemporary issues related to clinical practice in patients with severe AS: (1) under-referral/underuse of surgical aortic valve r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Additionally, the presence of left ventricular impairment represents a high-risk feature that mandates intervention in these patients. Still, some argue that it may already be too late when the LVEF drops 21 22. So far, there has been an ongoing debate with studies demonstrating a low risk of death in patients with asymptomatic aortic stenosis unless there is very severe aortic stenosis or signs of rapid progression or myocardial impairment 23 24.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the presence of left ventricular impairment represents a high-risk feature that mandates intervention in these patients. Still, some argue that it may already be too late when the LVEF drops 21 22. So far, there has been an ongoing debate with studies demonstrating a low risk of death in patients with asymptomatic aortic stenosis unless there is very severe aortic stenosis or signs of rapid progression or myocardial impairment 23 24.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis for symptomatic AS is typically poor. 14 The cumulative 1-year incidence of aortic valve-related death and heart failure is significantly higher in patients with than without symp-was considered statistically significant. All statistical analyses were performed using JMP 14.0 (SAS Institute Inc., Cary, NC, USA).…”
Section: Discussionmentioning
confidence: 99%
“…To support this view, clinical studies and meta-analyses have shown that survival in patients with AS and no or minimal symptoms at diagnosis is poor when LVEF is <60% (109)(110)(111)(112). Moreover, in asymptomatic AS patients with LVEF >60%, early AVR has been shown to be associated with reduced all-cause mortality, acute myocardial infarction, stroke, and hospitalization for HF, compared with patients treated with conservative management and AVR deferred after symptoms onset (113)(114)(115)(116)(117). To avoid the latter, alternative parameters, such as GLS, may be more useful to identify early myocardial function changes and the optimal timing for AVR (118,119).…”
Section: Aortic Stenosis (As)mentioning
confidence: 99%